Features of the Creative Method of Karl Marx - Bersenyov, Vladimir Leonidivich (Economy of Regions, 2018)
Reflections on the features of Karl Marx’s creative method (1818-1883) are presented in the genre of intellectual history. In this framework, I analyse the influence of exogenous and endogenous factors on the research process, on the personality of the scientist as well as on the choice of the directions of scientific inquiry, etc. In this respect, the 200th anniversary of the scientist’s birth provides an excellent opportunity to consider various features of his scientific activity and how a variety of reasons influenced it. Along the description of K. Marx’s life, I revealed and characterized such peculiarities of his creative method as the interdisciplinary nature of research activity, thorough and comprehensive selection of material for analysis, the desire to prove each theoretical position in several ways, the ability to recognize the limitations of his capabilities, and the readiness to correct his position. However, K. Marx remained true to his two mottos. One of them is “De omnibus dubitandum”, which distinguished him as a scientist, since it is doubt that creates the need for the analysis of phenomena of the surrounding world. The other one, “Nihil humani a me alienum puto”, testified that K. Marx was an ordinary man with his weaknesses, shortcomings, etc. For example, he usually published only the first parts (volumes) of his iconic works. In general, K. Marx as a scientist and as a man managed to give an intellectual charm to the idea of a proletarian revolution. Moreover, Marxism is still in demand as a research area of social sciences.